Peningkatan Kemampuan Membaca Permulaan dengan Media Kartu Huruf pada Siswa Kelas 1 Sekolah Dasar Inpres Onekore 6 Kecamatan Ende Tengah - Maria Margareta Bheni (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
This study examines the improvement of reading skills beginning with letter card media in Grade 1 Students of Inpres Onekore 6 Elementary School, Central Ende District. The research objective was to determine the beginning reading ability with letter card media. Classroom Action Research is a research method used in this study with four phases, namely planning, taking action, observing, and reflecting. In this study, the instruments used were reading manuscripts and assessment sheets. Reading manuscripts and assessment sheets are used to measure students 'reading ability, based on the minimum ability criteria (KKM) set in the Indonesian field of study, namely 70. Students' initial reading ability is measured using 3 criteria, namely pronunciation or speech, intonation, and fluency. when reading text. The results showed that there was an increase in the ability to start reading with letter card media in students, namely each aspect of pronunciation from cycle 1 to cycle 2 to 70%, intonation aspect 70%, and reading fluency by 73%.